Knowledge of Physical Education Study Program Students, National Islamic University of Indonesia Regarding Sexual Harassment - Fajrinur, Fajrinur; Sri Novayanti; Mirza, Mirza; Ivvon Septina Bella; Rizka Sylvia (Jurnal Multidisiplin Sahombu, 2025)
This study aims to determine the level of knowledge of Physical Education Study Program Students, Kebangsaan Islamic University of Indonesia about Sexual Harassment. This study uses a quantitative descriptive approach using a questionnaire as its instrument. Participants in this study were 28 students who were studying at the Faculty of Teacher Training and Education, Physical Education Study Program, Kebangsaan Islamic University of Indonesia in the even semester of 2024-2025. Based on the research that has been conducted, most students of Kebangsaan Islamic University of Indonesia understand that sexual harassment can be in the form of touching, verbal, written and visual, but some students misinterpret sexual harassment and sexual violence. Students' answers vary regarding what examples of sexual harassment are influenced by what sexual harassment means to them. The most common answers from students are about sexual harassment that occurs online or digitally. Very few students have ever seen sexual harassment or even experienced it. However, according to the students' answers above, it shows that if they see sexual harassment happening, they will report it or seek help or just tell someone else.